2017
DOI: 10.1097/mao.0000000000001567
|View full text |Cite
|
Sign up to set email alerts
|

Vertigo in Vestibular Schwannoma Patients Due to Other Pathologies

Abstract: Objective: To report findings from a cohort of vestibular schwannoma (VS) patients presenting with vertigo from a secondary comorbid vestibular disorder; and to discuss management strategies for this subset of patients presenting with both episodic vertigo and VS. Patients: All VS patients who presented with vertigo as the primary symptom from 2012 to 2015 and endorsing no other major complaints were examined. Intervention: Treatment with migraine lifestyle and prophylactic therapy, or Epley maneuver. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Correct diagnosis enhances appropriate intervention and resolution of vertigo. [19] While the resolution of vertigos appears to be common, recurrence can occur for various reasons. Recurrent attack of vertigo has been reported to be usually milder than that of the previous attack, [12] but it can be associated with fear, anxiety and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Correct diagnosis enhances appropriate intervention and resolution of vertigo. [19] While the resolution of vertigos appears to be common, recurrence can occur for various reasons. Recurrent attack of vertigo has been reported to be usually milder than that of the previous attack, [12] but it can be associated with fear, anxiety and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Dizziness in VS patients is a commonly experienced symptom that could be related to a variety of causes other than the tumor itself. In a retrospective cohort study on examining secondary causes of vertigo in VS patients at a tertiary center, Sahyouni et al found that 78% had comorbid VM [11]. Therefore, it is imperative to evaluate dizziness in VS patients using a wide differential diagnosis as part of their workup and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al report that 32% of VS patients developed vestibular dysfunction within six months of SRS [18]. This highlights the importance of dizziness evaluation and treatment as part of the comprehensive management of VS. A recent interventional study reports that all patients with VS and comorbid VM had complete symptomatic resolution of their vertigo after being treated with migraine prophylactic therapy (e.g., verapamil, topiramate, nortriptyline) and undergoing migraine diet and lifestyle changes [11]. In a non-placebo randomized controlled trial, both venlafaxine and propranolol were found to reduce vertigo episodes and severity in VM patients.…”
Section: Discussionmentioning
confidence: 99%
“…A complete history, CT scan, and audiometry are used for diagnosis, and treatment usually consists of surgical repair. 1 Treatment is best performed using an intratympanic blood patch and if unsuccessful potentially surgical repair. 2…”
Section: Diagnosis: Labyrinthitismentioning
confidence: 99%